DIALOGUES IN LEARNING: EVALUATING UNDERGRADUATE TEXTBOOKS AT AN-NAJAH NATIONAL UNIVERSITY - Al-Masri, Fatima Ahmed; Mahmoud , Jamal Abu-Hussein (International Research Journal of Arts and Communication, 2024)
Textbooks play a pivotal role in education, serving as the cornerstone of teaching and learning processes. They provide essential content, activities, and guidance necessary for both learners and teachers to achieve educational objectives effectively. Scholars emphasize the significant influence of textbooks on fostering independent and responsible learning among students. A good textbook not only equips learners with the necessary knowledge and skills but also encourages them to take ownership of their learning journey. Additionally, textbooks are invaluable resources for educators, simplifying lesson planning, enhancing learner comprehension, and optimizing instructional efficiency. This abstract explores the multifaceted importance of textbooks in education, drawing insights from scholarly literature to underscore their indispensable role in promoting effective teaching and learning practices